Degrowth and the global South: The twin problem of global dependencies - Claudius Gräbner-Radkowitsch; Birte Strunk (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2023)
We conduct a systematic literature review comprising both a quantitative and qualitative content analysis of the academic degrowth literature considering the Global South, and delineate substantive and methodological implications for future research. We find two main narratives: one stressing synergies, i.e. commonalities among Global South and Global North perspectives on degrowth, and another highlighting challenges, i.e. a constructive discussion of a range of challenges that emerge in this context. Our review reveals, inter alia, that the existing literature focuses mainly on the synergy narrative, and that there is a strong focus on theoretical and qualitative methodology. We argue that future research might want to put more emphasis on the investigation of structural dependencies between the North and South, using a broader methodological toolkit than so far. Only then one can effectively address the twin problem of global dependencies: the fact that within the current institutional framework, these dependencies are a motivation for and a potential obstacle to degrowth at the same time.
Keywords: 330; Degrowth; Global South; structural dependencies; decolonization